Antitumoural activity of a cytotoxic peptide of Lactobacillus casei peptidoglycan and its interaction with mitochondrial-bound hexokinase. Issue 7 (August 2016) - Fichera, Giuseppe A.; Fichera, Marco; Milone, Giuseppe
Abstract : In a previous study, we reported the cytotoxic activity against various tumour cells of the peptidoglycan of Lactobacillus casei . To isolate the most active components, we performed column-chromatography separation of the peptidoglycan complex and tested the related fractions for their cytotoxic activity. The most active fractions were then lyophilized and the residue was analysed by gas chromatography for its amino acid content and composition. On the basis of the known chemical formula of the basic peptidic component of the peptidoglycan complex of L. casei, a peptide was then synthesized [Europ. (CH-DE-FR-GB) Patent number 1217005; IT number 01320177] and its cytotoxicity was tested against tumoural and normal cells. The synthetic peptide was found to impair the entire metabolism of cultured tumour cells and to restore the apoptotic process. By contrast, normal cells appeared to be stimulated rather than inhibited by the peptide, whereas primary mouse embryo fibroblasts behaved similarly to tumour cells. On the basis of these results, L. casei peptidoglycan fragments and their constituent basic peptide might be applicable as potent antitumour agents. Abstract : Supplemental Digital Content is available in the text.